EDUCATION AND POLITICAL DA'WAH IN THE THOUGHT OF KH. ABDURRAHMAN WAHID: AN ANALYSIS OF CITIZENSHIP VALUES AND PLURALISM - Khairiyah, Nanda; Sirojuddin, Sirojuddin; Yasin, Rahman (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2025)
This study investigates the educational and political da'wah thought of KH. Abdurrahman Wahid (Gus Dur), emphasizing the intertwined values of citizenship and pluralism within the Indonesian Islamic context. As a renowned Muslim intellectual, former President, and social reformer, Gus Dur envisioned Islam as a moral force that upholds democracy, respects human rights, and nurtures interfaith harmony. Employing a qualitative-descriptive approach, this research draws upon an extensive literature review and content analysis of Gus Dur’s writings, speeches, and public interventions. The study reveals that Gus Dur’s da'wah was not limited to ritualistic preaching but extended into socio-political advocacy rooted in inclusive education. His concept of “civic Islam” sought to transcend ethnic, religious, and ideological boundaries, emphasizing universal values such as justice, tolerance, and human dignity. He actively challenged sectarianism and authoritarianism, positioning Islam as compatible with democratic governance and civil society. Furthermore, Gus Dur’s political da'wah prioritized the protection of minority rights and the preservation of national unity, framing diversity as a divine gift rather than a threat. These insights contribute significantly to contemporary discourses on Islamic education, da'wah strategies, and the role of religion in multicultural societies. The study concludes that Gus Dur’s legacy offers a transformative model for integrating religious, civic, and pluralist values in the Muslim world.